Development of Islamic Boarding Schools Through Local Wisdom-Based Community Economic Empowerment: An Innovative Offer - Rahmat Ramdhani; Zelvia Liska Afriani; Syukraini Ahmad; Ismail Ismail (Madania: Jurnal Kajian Keislaman, 2023)
This study aimed to analyze and document the internalizing Islamic boarding school development process through the empowerment of local wisdom and evaluate the innovative impacts of this approach. The research method used was a qualitative approach through case studies of Islamic boarding schools that have implemented local wisdom internalization strategies. The internalization process involves steps such as analysis of local needs, integration of local wisdom values in the curriculum, active involvement of Islamic boarding schools in local community activities, and the formation of partnerships with local governments and related stakeholders. By collecting data through interviews, observations, and document analysis, this research presents findings on the effectiveness of the internalization method. The research results show that Islamic boarding schools that adopt this innovative offer can produce graduates who are not only competent in the field of religion but also skilled in applying local wisdom in everyday life. In general, the Al-Qur’an offers two principles in community economic empowerment activities: the principle of ta'awun and the principle of shura. The principle of ta'awun is the principle of cooperation between various parties. The principle of syura is the deliberation between the government and institutions related to this community economic empowerment program. There are at least three economic business offers to empower the local wisdom-based community economy in Islamic boarding schools: community and Islamic boarding school collaboration in plantation management, batik-making skills business, and community collaboration with Islamic boarding schools in livestock management. Penelitian ini bertujuan untuk menganalisis dan mendokumentasikan proses internalisasi pengembangan pesantren melalui pemberdayaan kearifan lokal dan untuk mengevaluasi dampak inovatif dari pendekatan tersebut. Metode penelitian yang digunakan adalah pendekatan kualitatif melalui studi kasus pesantren yang telah menerapkan strategi internalisasi kearifan lokal. Proses internalisasi ini melibatkan langkah-langkah seperti analisis kebutuhan lokal, integrasi nilai-nilai kearifan lokal dalam kurikulum, pelibatan aktif pesantren dalam kegiatan masyarakat lokal, dan pembentukan kemitraan dengan pemerintah daerah dan stakeholders terkait. Melalui pengumpulan data melalui wawancara, observasi, dan analisis dokumen, penelitian ini menyajikan temuan tentang efektivitas metode internalisasi tersebut. Hasil penelitian menunjukkan pesantren yang mengadopsi tawaran inovatif ini mampu menghasilkan lulusan yang tidak hanya kompeten dalam bidang agama, tetapi juga terampil dalam menerapkan kearifan lokal dalam kehidupan sehari-hari. Secara umum ada dua prinsip yang ditawarkan Al-Qur’an dalam kegiatan pemberdayaan ekonomi masyarakat, yaitu prinsip ta’awun dan prinsip syura. Prinsip ta’awun adalah prinsip kerja sama dan sinergi diantara berbagai pihak. Prinsip syura bermakna musyawarah antara pemerintah dengan lembaga yang terkait dengan program pemberdayaan ekonomi masyarakat ini. Setidaknya, ada tiga tawaran usaha ekonomi dalam upaya pemberdayaan ekonomi masyarakat berbasis kearifan lokal di pesantren, yaitu kolaborasi masyarakat dan pesantren dalam pengelolaan perkebunan, usaha ketrampilan membuat batik, dan kolaborasi masyarakat dengan pesantren dalam pengelolaan peternakan.